Noninvasive Imaging of Myocardial Ischemia - Anagnostopoulos, Constantinos; Nihoyannopoulos, Petros; Bax, Jeroen; Wall, Ernst van der (Springer London : Imprint: Springer, 2006)
Non-invasive imaging plays a very important role in the assessment of patients investigated for coronary artery disease, providing valuable information for diagnosis and aiding management decisions. It covers a broad spectrum of investigations including radionuclide imaging, echocardiography, magnetic resonance imaging and computed tomography. Progress towards the most efficacious means of assessing a patient is relentless, with recent years seeing an important shift in emphasis from invasive to noninvasive techniques. This informative book compares the various modalities in a practical diagnostic environment. It thus provides a forum for fertile discussion, bringing the discussion of these various methodologies together in one reference for the first time. The narrative flow is unique and will ensure that all levels of medical practitioners with an interest in cardiac imaging will find this an unparalleled resource for use in guiding their practice.